Structural and theoretical investigations of the Rh(III) and Co(III) complexes containing symmetrical edta-type ligands with mixed carboxylate and diamine rings: Quantum-mechanical/NBO insight into stability of geometrical isomers - Jeremić, Marija S.; Radovanović, Marko D.; Heinemann, Frank Wilhelm; Vasojević, Miorad M.; Matović, Zoran D. (Polyhedron, 2019)
The trans(O 5 O 6 ) isomer of the Na[Rh(eddadp)]·4H 2 O and the K[Co(eddadp)]·3H 2 O (eddadp = ethylenediamine-N,N′-diacetate-N,N′-di-3-propionate) were synthesized and Na[Rh(eddadp)]·4H 2 O structure was confirmed by X-ray diffraction analysis. The percentage of particular isomers found in reaction equilibrium mixtures of [M(eddadp)] − complex has been reported. Single crystal X-ray diffraction of the complex revealed an octahedral geometry of the Rh(III) centre. Improved structural distortion analysis of M(III) (M = Rh, Co) complexes with symmetric edta-type of ligands containing mixed carboxylate and diamine rings was made. Structural distortion analysis has determined high values of total deviation of the octahedral angles (Δ(O h )) for both existing trans(O 5 ) (34°) and trans(O 5 O 6 ) (41°) isomers of [Rh(eddadp)] − complex, while in the case of a similar Co(III) complex, relatively low value (31°) for trans(O 5 ) has been established. Extensive QM/NBO calculations were made for both systems [M(eddadp)] − and [M(1,3-pddadp)] − using different DFT methods (B3LYP/SDD, M06/SDD, MP2/SDD). By correlating the structural parameters obtained from X-ray and DFT optimized 3D structures, the B3LYP/SDD method was used as the method of choice. Based on the correlation between the energies of the optimized systems and the strain parameters, the existence of the trans(O 6 ) isomer of the [Rh(1,3-pddadp)] − complex was predicted. NRT (Natural Resonance Theory) analysis gave the best resonances for each isomer. Here the stability of particular isomer has been described in terms of 3-CHB bonds involving metal ions and Second Order Perturbation Theory analysis using Donor/Acceptor energies. Further, to explain the bonding nature of M-edta-type complexes the Natural Coulomb Electrostatics (NCE) analysis has been done as well. The pairwise steric exchange interaction E I,J pwx results obtained for the best-ranked resonances of different isomers are in excellent agreement with favored isomers reported so far. For the energy limit of the possibility of forming geometric isomers, a value of about 6 kcal mol −1 is proposed.
CRIS-Team Scopus Importer:2019-05-28
Keywords: DFT; NBO; Polyaminopolycarboxylates; Rhodium(III); X-ray